2012
DOI: 10.1136/bcr-2012-007568
|View full text |Cite
|
Sign up to set email alerts
|

Sjogren's syndrome with distal renal tubular acidosis presenting as hypokalaemic paralysis

Abstract: SummaryA young lady with a history of repeated episodes of generalised weakness and fatigue presented to our hospital with similar symptoms and was found to have severe hypokalaemia. She had been previously diagnosed as hypokalaemic periodic paralysis but during this presentation she had also started complaining of the classic sicca-complex of Sjogren's syndrome, which was not present previously. On subsequent investigations she was found to have normal anion-gap metabolic acidosis with positive urine anion ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…We later confirmed that the patient’s low-serum potassium and plasma HCO 3 − levels eventually normalized after a month. Taken together, these data suggested that the patient was probably suffering from distal renal tubular damage17 during the period of severe hypernatremia/hyperchloremia. Thereafter, the patient has fully recovered with no further disturbances of consciousness and with normal oral fluid intake, and continues to receive treatment for multiple myeloma.…”
Section: Case Reportmentioning
confidence: 62%
“…We later confirmed that the patient’s low-serum potassium and plasma HCO 3 − levels eventually normalized after a month. Taken together, these data suggested that the patient was probably suffering from distal renal tubular damage17 during the period of severe hypernatremia/hyperchloremia. Thereafter, the patient has fully recovered with no further disturbances of consciousness and with normal oral fluid intake, and continues to receive treatment for multiple myeloma.…”
Section: Case Reportmentioning
confidence: 62%
“…In the early diagnosis era of autoimmune diseases (like in rheumatoid arthritis), the importance of recognizing kidney involvement before glandular symptoms appear has been observed previously [ 21 , 25 , 28 ]. Also, we consider it important to determine whether some factors can trigger the beginning of this manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…Vaidya et al 2 described a young woman with hypokalaemic periodic paralysis subsequently diagnosed to have RTA with hypokalaemia. Unfortunately, the diagnosis of underlying Sjogren's syndrome was only made when the patient developed sicca symptoms.…”
Section: Discussionmentioning
confidence: 99%